Loss of Function but No Gain of Function Caused by Amino Acid Substitutions in the Hexapeptide of Hoxa1 In Vivo - Remacle, Sophie (American Society for Microbiology, 2004)
Homeodomain containing transcription factors of the Hox family play critical roles in patterning the anteroposterior embryonic body axis, as well as in controlling several steps of organogenesis. Several Hox proteins have been shown to cooperate with members of the Pbx family for the recognition and activation of identified target enhancers. Hox proteins contact Pbx via a conserved hexapeptide motif. Previous biochemical studies provided evidence that critical amino acid substitutions in the hexapeptide sequence of Hoxa1 abolish its interaction with Pbx. As a result, these substitutions also abolish Hoxa1 activity on known target enhancers in cellular models, suggesting that Hoxa1 activity relies on its capacity to interact with Pbx. Here, we show that mice with mutations in the Hoxa1 hexapeptide display hindbrain, cranial nerve, and skeletal defects highly reminiscent of those reported for the Hoxa1 loss of function. Since similar hexapeptide mutations in the mouse Hoxb8 and the Drosophila AbdA proteins result in activity modulation and gain of function, our data demonstrate that the functional importance of the hexapeptide in vivo differs according to the Hox proteins.